People with intellectual disabilities and their health care utilization in Korea. : A study using the Korea welfare panel study (KOWEPS). (Journal of Accessibility and Design for All, 2021)
Empirical studies on health care utilization by people with disabilities are rare in South Korea. There exist even fewer studies that examine health care utilization by people with intellectual disabilities and that compare the health care utilization pattern by this population vs by population with other types of disabilities. This study investigates the characteristics of people with intellectual disabilities (vs those with non-intellectual disabilities) and evaluates the relationship between the presence/absence of intellectual disabilities and health care utilization. The present study analyzed the 2005 and 2016 Korea Welfare Panel Study data. The final sample included observations from these two years that span over the ten-year period. Health care utilization was operationalized by whether the people with disabilities (intellectual and non-intellectual) participated in health screening, how often they received outpatient physician visits, and how long they received inpatients service. To examine the effect of the types of disabilities on health care utilization, random-effects logistic regression and negative binomial regression models were employed. The present study found that people with intellectual disability showed a much lower attendance rate than both people with non-intellectual disabilities and people without disabilities. The percentage of those who received outpatient service experience was higher for people with non-intellectual disabilities than for people with intellectual disabilities. The mean annual number of outpatient visits was greater for people with non-intellectual disabilities than for people with intellectual disabilities. People with intellectual disabilities also showed a lower rate of inpatient experience compared to those with non-intellectual disabilities. Based on these results, it is suggested that policy-makers should promote fuller access to the use of health care services for people with intellectual disability. In addition, more efforts should be made for people with intellectual disabilities to participate in medical research so that they can express their demands on health-related issues.